HAK JAMAAH HAJI ATAS HASIL PENGELOLAAN SETORAN AWAL BIAYA PENYELENGGARAAN IBADAH HAJI - Juju Jumena; Ilham Bustomi; Siti Fatimah (IAIN Syekh Nurjati Cirebon, 2018)
Abstract Cooperative as a manifestation of the economic development of democracy. This happens when the cooperative is well managed, The existence of cooperatives in the District of Gunungjati has not described the cooperative as a form of economic development populist.This study aims to answer from the questions that become the formulation of the problem, how SWOT Cooperative as a Form of Community Economic Development in the District of Gunungjati? This research uses qualitative research,The data collected by interview technique (interview), observation, documentation and then analyzed by descriptive method of analysis.The SWOT analysis results that can be submitted by the authors are the cooperatives in the District of Gunungjati has the power in management,And has a weakness of the level of public confidence,Besides the cooperative opportunities for cooperation with financial institutions are very open,On the other hand the threat is the ease of provision of borrowers of informants (middlemen) who are still very difficult to overcome. Keywords: Cooperative, SWOT Analysis, and Community Economic. Abstrak Koperasi sebagai wujud dari pembangunan ekonomi kerakyatan. Hal ini terjadi apabila koperasi dikelola dengan baik, keberadaan koperasi di Kecamatan Gunungjati belum mendiskripsikan koperasi sebagai wujud pembangunan ekonomi kerakyatan. Penelitian ini bertujuan untuk menjawab dari pertanyaan-pertanyaan yang menjadi rumusan masalah, bagaimana SWOT Koperasi Sebagai Wujud Pembangunan Ekonomi Kerakyatan di Wilayah Kecamatan Gunungjati? Penelitian ini menggunakan penelitian kualitatif, data yang dikumpulkan dengan teknik interview (wawancara), observasi, dokumentasi kemudian dianalisis dengan metode deskriptif analisis. Adapun hasil analisis SWOT yang dapat disimpulkan oleh penulis adalah koperasi-koperasi di Kecamatan Gunungjati memiliki kekuatan di manajemen, dan mempunyai kelemahan dari tingkat kepercayaan masyarakat, selain itu peluang koperasi untuk kerjasama dengan lembaga keuangan sangat terbuka, disisi lain ancamannya adalah kemudahan penyediaan pinjam informan (tengkulak) yang masih sangat sulit diatasi.Kata Kunci: Koperasi, Analisis SWOT, dan Ekonomi Kerakyatan.